Towards a Framework for Social Media Applications in Consumer Health - Sajjad, Jawad; Ruhi, Umar (Université d'Ottawa | University of Ottawa, 2013)
As social media applications have now become a part of daily life for many individuals, there is no doubt that it is changing the way patients communicate in the modern age. This paper will try to examine the key concepts, tools, frameworks, preliminary work and trends for the future of Social Media in healthcare. Additionally, it will also analyze recent case studies related to the actual implementation of social media in healthcare and the results achieved through its use. Finally, this paper will provide a conceptual framework that integrates various forms of social media with Health 2.0 use-cases in consumer health.
Keywords: Consumer Health Informatics; Health 2.0; Medicine 2.0; Healthcare